The Documentation Status Continuum and the Impact of Categories on Healthcare Stratification - Tiffany Denise Joseph (Social Sciences)
Public discourse on immigration and social services access has been contentious in immigrant-receiving countries. Scholars have examined immigrants’ marginalization as a form of civic stratification, where boundaries based on documentation status affect immigrants’ experiences and benefits granted by the state. This scholarship lacks a framework outlining existing documentation status categories and does not fully answer three research questions I pose in this article: (1) what is the alignment of documentation status categories relative to each other, (2) how does policy (re)configure those categories over time, and (3) how have documentation status categories shaped access to health care in the United States? This article answers those questions and argues that the documentation status continuum (DSC) framework fills these gaps. In the DSC, undocumented immigrants are at one end and citizens are at the other, with many documentation statuses in between. Public policy creates these statuses and generates stratification through allocating benefits based on one’s DSC position. Policy also shapes movement along the continuum, which shapes benefits eligibility. Using the 2006 Massachusetts Health Reform and national 2010 Affordable Care Act (ACA) Reform as policy examples and interviews conducted with 207 immigrants, healthcare professionals, and immigrant organization employees in Boston, this article demonstrates how healthcare access is stratified along the DSC between citizens and noncitizens. This has implications for various outcomes that social scientists examine amid increasing anti-immigrant sentiment in the US and beyond.